2021
DOI: 10.7759/cureus.14223
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Diabetic Ketoacidosis: Report of Eight Cases

Abstract: To describe the clinical characteristics and outcome of hospitalized COVID-19 patients with diabetic ketoacidosis (DKA). MethodsWe report eight cases of diabetic ketoacidosis in COVID-19 who presented to our institution in New Jersey, USA. COVID-19 was diagnosed by nasopharyngeal swab reverse transcription polymerase chain reaction (RT-PCR). The patients' electronic medical records were reviewed. Data on patients' age, sex, ethnicity, laboratory values, glycosylated hemoglobin level, oral antihyperglycemic age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
0
6
1
Order By: Relevance
“…pH of < 7) has been identified as an important predictor of mortality in patients with DKA and COVID-19 compared to those who survived ( p = 0.047) [ 90 , 91 ]. Very high uncontrolled random blood glucose level (> 1000 mg/dl) was the other biochemical parameter at presentation that differed significantly between the survival and death groups in DKA patients infected with SARS-CoV-2 ( p = 0.048); a finding suggested in previous studies [ 91 , 95 , 96 ] and in contradiction with data from case reports demonstrating death in DKA cases during COVID-19 infection when their blood glucose levels were kept at < 500 mg/dl [ 27 , 59 , 63 ]. Moreover, increasing age in combination with male gender and BMI ≥ 30 might denote seriously sick patients who can potentially have more morbidity and propensity to die.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…pH of < 7) has been identified as an important predictor of mortality in patients with DKA and COVID-19 compared to those who survived ( p = 0.047) [ 90 , 91 ]. Very high uncontrolled random blood glucose level (> 1000 mg/dl) was the other biochemical parameter at presentation that differed significantly between the survival and death groups in DKA patients infected with SARS-CoV-2 ( p = 0.048); a finding suggested in previous studies [ 91 , 95 , 96 ] and in contradiction with data from case reports demonstrating death in DKA cases during COVID-19 infection when their blood glucose levels were kept at < 500 mg/dl [ 27 , 59 , 63 ]. Moreover, increasing age in combination with male gender and BMI ≥ 30 might denote seriously sick patients who can potentially have more morbidity and propensity to die.…”
Section: Discussioncontrasting
confidence: 58%
“…Among the included studies, 11 reported DKA and COVID-19 in children [ 8 , 11 , 22 , 30 , 34 , 44 , 45 , 56 , 61 , 66 , 72 ], 56 reported DKA and COVID-19 in adults [ 9 , 10 , 12 21 , 23 , 25 29 , 31 33 , 35 43 , 46 55 , 57 – 60 , 62 65 , 67 71 , 73 75 ], and only 1 study reported DKA and COVID-19 in both children and adults [ 24 ]. There were 54 case report [ 8 12 , 14 , 16 , 17 , 19 23 , 25 27 , 29 42 , 44 51 , 53 58 , 60 , 61 , 64 , 66 , 67 , 69 , 71 , 72 , 74 , 75 ], 10 case series [ 13 , 15 , 28 , 43 , 58 , 59 , 62 , 63 , 70 , 73 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease severity and disease progression were also worse in the COVID-19 cohort as represented by vasopressor data, dialysis use, and intubation rates. Mechanically ventilated patients with COVID-19 and DKA have been shown to have worse outcomes while patients with diabetes have also been shown to have longer lengths of stay compared to patients without diabetes according to previously published case reports ( 19 ).…”
Section: Discussionmentioning
confidence: 82%
“…7.5 million adults aged 18 and older were unaware of their diagnosis, accounting for 2.8% of all adults in the United States and 21.4% of all persons with diabetes. 4 DKA is the most prevalent hyperglycemic crisis, which also includes HHS and the overlap syndrome of DKA and HHS, known as hyperosmolar ketoacidosis. DKA occurs when there is a relative or absolute insulin deficiency, resulting in decreased glucose utilization and unhindered lipolysis, leading to higher ketone body formation and eventually metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%